EVALUASI KINERJA TRANSPLANTASI Acropora Sp. MENGGUNAKAN RAK BESI PADA KONDISI HIDRODINAMIKA MUSON DI GOSONG KALANGAN, LAMPUNG - Priyanatha, Dzulfikar Yusuf; Royani, Vika Aulia; Nugraha, M. Aqwam; Az Zahra, Flora Bintang; Simatupang, Dwi Rani Asfarini; Mutia, Aprila; Farid, Muhammad Faiz; Armando, M Zona Bintang; Priyanto, Davit Agus; Afifi, Mohammad Hafizh; Nayla, Azza Dera Rahma; Priyambodo, Priyambodo; Taufik, Nadya Syifa; Siringo-ringo, Regina Stephani Mesina; Manik, Lastiarma; Azzaid, Fahrez Isnanta; Master, Jani; Ikhsanudin, Ahmad; Fathiyya, Naila Nur (Jurnal Biogenerasi, 2026)
Coral reef ecosystems in Gosong Kalangan waters are experiencing degradation, thereby requiring effective rehabilitation efforts, one of which is coral transplantation of Acropora sp. using artificial media in the form of iron racks. This study aimed to analyze the survival rate and growth rate of Acropora sp. fragments transplanted using this method. The research was conducted as a field experiment employing a Completely Randomized Design (CRD) over a six-month period (July to December 2025) at a depth of approximately ±4 meters. The main parameters observed were survival rate and linear growth of coral fragments. The results showed a decline in survival rate from 100% in the first month to 56% at the end of the observation period. In contrast, the surviving fragments exhibited an increase in average length from 9.4 cm to 14.64 cm (total growth of 5.39 cm), with a mean growth rate of 0.898 cm per month. The decrease in survival rate was presumably influenced by biotic pressure in the form of predation by Drupella sp., as well as abiotic disturbances related to hydrodynamic factors and monsoonal waves affecting the stability of the transplantation racks. The iron rack method was able to support the growth rate of Acropora sp. fragments; however, its effectiveness in maintaining survival is highly dependent on the stability of local environmental conditions.